Development of Smart Card Learning Media Based on the Make A Match Model on Procedure Text Material in High Schools - Dwi Jonanda Putri; Mangatur Sinaga; Silvia Permatasari (CV. Rayyan Dwi Bharata, 2024)
This research is a type of research and development (RD). The problem formulation in this research is how to develop procedures, quality and practicality of smart card-based learning media with a make a match model in procedural text material in high school. The test subjects in this research were class XI students at SMAN 6 Pekanbaru, totaling 30 students. The data in this research was obtained from the results of potential and problem analysis as well as limited trials with students. The data sources in this research were obtained from interviews, questionnaire distribution, and literature study. The data in this study were analyzed using descriptive statistics in the context of averages and Pearson product moment correlations. The quality of the make a match model of smart card-based learning media in procedural text material in high school is seen from the results of expert validation analysis and received a very good assessment. Its practicality can be seen from the results of the analysis of student assessments in limited trials and an assessment was obtained in the very good category